2001
DOI: 10.2135/cropsci2001.1809
|View full text |Cite
|
Sign up to set email alerts
|

Ear Temperature and Pollination Timing Effects on Maize Kernel Set

Abstract: Maize (Zea mays L.) kernel set can be improved through synchronous pollination within and between ears. Reductions in kernel set could be expected because of asynchronous pollination between early‐ and late‐appearing silks. We analyzed the effect of (i) selective ear heating around the time of silking, and (ii) different time gaps between early‐ and late‐pollinated silks in an attempt to modify kernel set. Tip ear heating was expected to minimize the advantage of early silking ovaries. Lateral heating and poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 26 publications
2
72
0
Order By: Relevance
“…In any given season, a corn crop can be subject to general abiotic and biotic stresses such as excess or insufficient moisture, excessive temperature, and disease, insect, and weed pressure, creating increased competition for resources (Carcova and Otegui, 2001;Stanger and Lauer, 2007;Tollenaar and Wu, 1999). A common stress response is increased anthesis-silking interval (ASI), the period between 50% pollen shed and 50% silking (Brekke et al, 2011b;Daynard and Muldoon, 1983;Edmeades and Daynard, 1979;Tokatlidis et al, 2011;Tokatlidis and Koutroubas, 2004).…”
Section: General Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…In any given season, a corn crop can be subject to general abiotic and biotic stresses such as excess or insufficient moisture, excessive temperature, and disease, insect, and weed pressure, creating increased competition for resources (Carcova and Otegui, 2001;Stanger and Lauer, 2007;Tollenaar and Wu, 1999). A common stress response is increased anthesis-silking interval (ASI), the period between 50% pollen shed and 50% silking (Brekke et al, 2011b;Daynard and Muldoon, 1983;Edmeades and Daynard, 1979;Tokatlidis et al, 2011;Tokatlidis and Koutroubas, 2004).…”
Section: General Stress Tolerancementioning
confidence: 99%
“…A longer ASI reduces the chance that all female spikelets will be pollinated and thus increases the potential for yield reduction (Carcova et al, 2000;Monneveux et al, 2006;Sangoi, 2000). Carcova and Otegui (2001) reported that under high plant density, improved kernel set leading to improved grain yield was associated with a shorter ASI.…”
Section: General Stress Tolerancementioning
confidence: 99%
“…Bolanos and Edmeades (1996) showed that close synchrony between male and female inflorescence is desirable to improve yield and yield components. An asynchronous flowering may limit grain production per ear due to lack of pollen, lost of silk receptivity or early kernel abortion caused by dominance of early formed ovaries from the base of the ear on the late formed from the tips (Carcova, Otegui, 2001). In agreement with the results of the present study, increase in ASI was reported with increase in plant density (Amanullah et al, 2009).…”
Section: Time Gap Between Anthesis and Silking (Asi)mentioning
confidence: 99%
“…Edmeades et al (2000) showed that close synchrony between male and female inflorescence was desirable to improve kernel set and yield of corn. An asynchronous flowering may limit grain production per ear due to lack of pollen, loss of silk receptivity or early kernel abortion caused by the dominance of early formed ovaries from the base of the ear on the late formed from the tips (Carcova, Otegui, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it might be possible to sustain pollen viability by upregulating HSP genes shown to be active earlier in pollen development or by selecting for slower pollen dehydration. Kernel set can be improved, particularly at high temperature, by increasing the synchrony of pollination within and among ears (Carcova and Otegui 2001). They observed pollination gaps of 2-4 days reduce kernel number per ear up to 51%; the impact of asynchronous pollination was increased by exposure to high temperatures.…”
Section: Temperature Effects On Maize Growth and Yieldmentioning
confidence: 99%